How i survived middle school : P.S. I really like you - Krulik, Nancy E. (New York : Scholastic, 2008)
Jenny tries to find out the identity of a secret admirer who has been sending her notes, but is distracted from her mystery when her friends Felicia and Rachel become entangled in a big argument.
"Apple series"--P. [4] of cover.
RL4.
008-012.
Accelerated Reader/Renaissance Learning
Keywords: Middle school students -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Middle school students -- Fiction; Interpersonal relations -- Fiction